Adsorption removal of methyl violet from aqueous solution by chromium phosphovanadate. (15th September 2020) - Zhai, Haoying; Zou, Jinshan; Liu, Fuming; Chen, Fangyuan; Yan, Xingrong; Zhou, Wen‐Jun
Abstract : An effective adsorbent for methyl violet (MV), chromium phosphovanadate (named as Cr‐PV) nanomaterials, was prepared by a simple coprecipitation strategy. The microstructure and morphology of as‐synthesized Cr‐PV were characterized by SEM, X‐ray diffraction (XRD), X‐ray photoelectron spectroscopy (XPS), and Fourier transform infrared (FTIR), respectively, which was confirmed as nanosheet shapes. The adsorption behavior for MV from aqueous solutions was systematically investigated. The kinetic and equilibrium results indicate that the adsorption process follows pseudo‐second‐order kinetic model and Langmuir isotherm, respectively. Compared with PV and commercially available activated carbon, Cr‐PV has preferable adsorption property to MV. The maximum adsorption capacity can reach 123.81 mg g −1 at room temperature. The thermodynamic parameters such as Gibbs free energy (Δ G ο ), enthalpy (Δ H ο ), and entropy change (Δ S ο ) show that the adsorption of MV is an endothermic and spontaneous process. Moreover, the adsorptive behavior between Cr‐PV and MV is monolayer adsorption and electrostatic interaction mechanism. Cr‐PV, as a promising adsorbent with high adsorption capacity and fast adsorption rate, shows great potential for the removal of MV from wastewater.